2013
DOI: 10.1038/pr.2013.137
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and anthropometrics of 4-y-old children born after preimplantation genetic screening: follow-up of a unique, moderately sized, randomized controlled trial

Abstract: Background: Recent studies suggest that in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) are associated with suboptimal cardiometabolic outcome in offspring. It is unknown whether preimplantation genetic screening (PGS), which involves embryo biopsy, affects blood pressure (BP), anthropometrics, and the frequency of received medical care. Methods: In this prospective multicenter follow-up study, we assessed BP, anthropometrics, and received medical care of 4-y-old children born to women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…In this study, where only singletons born after PGT-M and PGT-SR but not after PGT-A were included, we did not find any difference in BMI at the age of 6 years. Only one other research group described anthropometric and blood pressure measurements at childhood ages in children born after embryo biopsy in a smaller study: at 4 and 9 years of age they found no differences between 43 children (29 singletons, 14 twins) born after IVF/ICSI with PGT-A and 56 children born after IVF/ICSI without PGT-A (Seggers et al , 2013; Kuiper et al , 2017). However, although embryo biopsy was also performed at Day 3 in the latter studies, outcomes in PGT-A children may not be extrapolated to PGT-M and PGT-SR children given the dissimilar indications and parental reproductive background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, where only singletons born after PGT-M and PGT-SR but not after PGT-A were included, we did not find any difference in BMI at the age of 6 years. Only one other research group described anthropometric and blood pressure measurements at childhood ages in children born after embryo biopsy in a smaller study: at 4 and 9 years of age they found no differences between 43 children (29 singletons, 14 twins) born after IVF/ICSI with PGT-A and 56 children born after IVF/ICSI without PGT-A (Seggers et al , 2013; Kuiper et al , 2017). However, although embryo biopsy was also performed at Day 3 in the latter studies, outcomes in PGT-A children may not be extrapolated to PGT-M and PGT-SR children given the dissimilar indications and parental reproductive background.…”
Section: Discussionmentioning
confidence: 99%
“…But parents who opt for PGT-M or for PGT-SR are not necessarily infertile. Although data on outcomes after PGT-A are not directly transferable, Dutch reseachers reported that blood pressure and anthropometry in children conceived after IVF/ICSI with or without PGT-A did not differ at the age 4 and 9 years (Seggers et al , 2013; Kuiper et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, data on developmental status and health of PGT‐A offspring is scarce (Figure ). From the paper by Mastenbroek et al, six prospective, assessor‐blinded follow‐up studies were derived on children born to women undergone PGT‐A or not, to evaluate neurodevelopmental outcomes at 18 months, 2, 4 and 9 years . In these studies, no statistically significant differences in mental, psychomotor, neurological and behavioral outcomes were reported between children born after PGT‐A and those born without PGT‐A.…”
Section: Threatsmentioning
confidence: 99%
“…From the paper by Mastenbroek et al, 1 six prospective, assessor-blinded follow-up studies were derived on children born to women undergone PGT-A or not, to evaluate neurodevelopmental outcomes at 18 months, 2, 4 and 9 years. [85][86][87][88][89][90] In these studies, no statistically significant differences in mental, psychomotor, neurological and behavioral outcomes were reported between children born after PGT-A and those born without PGT-A. Unfortunately, the power calculation of the original RCT was based on the number of women needed to detect an increase in ongoing pregnancy rates and not on the number of children to be followed-up.…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…All participating children were born to subfertile parents, i.e., couples who were not able to conceive after 12 months of unprotected sexual intercourse. Fouryear-old outcomes of the Groningen assisted reproduction technique cohort singletons born after ovarian stimulation and IVF and that of the PGS singletons conceived without PGS have been reported previously Seggers et al, 2013Seggers et al, , 2014.…”
Section: Participantsmentioning
confidence: 99%